Extending the scope of practice for experienced assistant practitioners in breast screening and the impact on service resilience. Issue 4 (November 2022) - Zelenyanszki, C.; Vertenten, C.; Spencer, S.; Hudson, D.; Currie, R.
Abstract: Introduction: Historically, the NHS Breast Screening Programme (NHSBSP) required Assistant Practitioners (APs), who are non-registered practitioners, to be supervised by and work alongside a registered radiographer (RPs). Following a national pilot looking at the implementation of two APs working remotely without direct supervision by a radiographer, this study seeks to evaluate a local trial of this new model of working. Methods: Pairs of APs were deployed to work together on a mobile breast screening unit over a four-month period. Assessments were carried out to review technical performance using established NHSBSP technical repeat and recall rates in the United Kingdom. Notes on any queries from those involved during the dual AP sessions were prospectively collected and reviewed. Feedback from APs and other multi-disciplinary team members were collected and content analysis was applied. Results: A total of 828 women were screened across the 26 AP clinics that were delivered. Technical repeat and recall rates of participating APs remained stable throughout the pilot period and marginally improved across all participating staff. No women attended the AP clinic who could not be screened and no support from a RP was required during the sessions. Seven normal clinics were converted to AP clinics due to lack of staff on the day, avoiding the cancellation of screening clinics. Feedback from across the screening team was positive. Conclusions: Increasing the autonomy of experienced APs can significantly contribute to the delivery of a resilient radiographic workforce that maintains service performance. Suitable experience and wider team involvement appear to be keys to success in this case. Implication for practice: Increasing the autonomy and voice of the APs has a positive effect on the resilience of the wider radiographic workforce and the service as a whole. It also can provide a mechanism for raising their profile with a possible raise in job satisfaction, staff engagement and retention.